Pain treatment in patients with renal insufficiency - Gras-Ozimek, Jordi; Kozinska, Urszula (Journal of Education, Health and Sport, 2022)
Chronic pain is experienced by the majority of patients with renal insufficiency. Pain management in patients with chronic kidney disease is difficult because a significant part of painkillers is excreted through the kidneys, therefore side effects are more common among this population. The aim of this review is to draw attention to the available pain management options in patients with CKD based on an analysis of published articles. The following article is based on the literature found in the pubmed database. Treatment should include pharmacological, non-pharmacological methods and treatment of comorbidities, whereas patients should be carefully monitored for side effects and possible complications. More research is needed in this area.